Jääkiekkoilijoiden kynnyssykkeiden määrittäminen juoksun, luistelun ja pyöräilyn aikana - Laukkanen, Jesse (2023)
Ice hockey requires players to utilize both aerobic and anaerobic capacities. Optimal performance during the match requires the ability to react and perform in the various situations of the match, which require not only endurance, speed, and strength, but also tactical, technical, and quick decision-making skills. The performance of ice hockey players during the match is based on the right kind of systematic training and planning. Determined aerobic and anaerobic threshold heart rates in load monitoring are often used to support training planning. Over the years, the threshold heart rate assessments performed on hockey players using a cycle ergometer or running do not necessarily correspond to skating on the ice, because the movements take place in a cycle ergometer, running and skating in different ways. The purpose of this study is to determine and research the threshold heart rates of ice hockey players when loading is done by skating, cycling, and running. The subjects of this study (n = 15) were male players from the highest national level of youth ice hockey (U20). The measurement of this study was implemented as a 2-week cross-sectional study in the laboratory of the University of Jyväskylä and in the ice rink of Jyväskylä. The subjects completed Inbody measurement and three incremental threshold tests in a random order every two rest days. The incremental threshold tests were performed by running on a treadmill, cycling on a cycle ergometer, and skating a 100-meter track in an ice rink. Based on the results, individual and average differences in threshold heart rates between the methods were observed. A statistically significant difference was observed in the aerobic threshold between running (157 ± 11 bpm, p < 0.05*) and cycle ergometer (147 ± 12 bpm, p < 0.05*). At the anaerobic threshold running (179 ± 7 bpm, p < 0.05*) and skating (177 ± 5 bpm, p < 0.05*) differed statistically significantly from cycling (172 ± 5 bpm, p < 0.05*). To conclude, according to this study, the threshold heart rate assessments made with cycle ergometer and running do not correspond to skating on ice. For threshold heart rate assessments, in terms of monitoring, threshold tests should be implemented with the form of movement that want to be monitored.